Evolution of quality assurance in higher education from INQAAHE GGP to ISGs − Are quality assurance agencies in Asia ready to the emerging modules? - Angela Yung Chi Hou; Christopher Hong-Yi Tao; Kyle Zi-Wei Zhou; Arianna Fang Yu Lin; Edward Hung Cheng Su; Ying Chen (Emerald Publishing, 2024)
Purpose - In 2022, the International Network for Quality Assurance (QA) Agencies in Higher Education (INQAAHE) published the new guidelines by adding three QA modules in response to the changing higher education landscape. The paper aims to investigate the transformative focus of quality assurance in higher education globally as well as Asian response to three new QA modules according to the INQAAHE ISGs. Design/methodology/approach - The research conducted a quantitative approach for data collection. An on-line survey was conducted to perceive QA practices, perceptions toward new emerging QA modules and challenges encountered. In total, there were 26 responses from 18 territories with 22 QA agencies. A total of 13 out of them have a national qualifications framework in place. Findings - Three are three major findings in the study. First, national policy and criteria and standards in distance education have been developed in the majority of Asian nations. Second, non-signatories of the Tokyo Convention had a higher proportion of having related policies, regulations and criteria in CBHE and distance education. Third, national policies and regulations; and lack of professional staff are two common challenges implementing QA in new types of providers. Originality/value - The findings are of value for policymakers, QA agencies and universities to advocate the new QA model as a systematic approach in response to changing higher education landscape in the post pandemic era.